A SIMULATION STUDY OF DEPOSITION PARAMETERS FOR 129I DISCHARGED FROM THE ROKKASHO REPROCESSING PLANT. Issue 3 (26th April 2019) - Abe, Koichi; Hasegawa, Hidenao; Akata, Naofumi; Kakiuchi, Hideki; Chiang, Jing-Hsien; Suwa, Hiroji; Hisamatsu, Shun'ichi
Abstract: The first commercial spent nuclear fuel reprocessing plant at Rokkasho in Japan discharged 129 I from actual spent nuclear fuel into the atmosphere during its test operation from 2006 to 2008. Previously, we measured monthly atmospheric concentrations of gaseous and particulate 129 I and atmospheric deposition rates of 129 I from the campus of our institute, which is 2.6 km east of the main stack of the plant. In this study, we simulated the atmospheric concentrations and deposition rates of 129 I using a combination of the Fifth-Generation Penn State/NCAR Mesoscale Model and the improved CG-MATHEW/ADPIC models, Version 5.0. Here, we report on the optimised deposition parameters of 129 I used to simulate the measured values using 129 I atmospheric discharge rates from the main stack.